PENGARUH PRETREATMENT JERAMI PADI PADA PRODUKSI ENZIM TERMOSTABIL MENGGUNAKAN ISOLAT BAKTERI TERMOFILIK: (The Effect of Rice Straw Pretreatment on Thermostable Enzyme Production Using Thermophilic Bacteria Isolate) - Sunrixon Carmando Yuansah; Darmawan Darmawan; Nurdian Fitriana; Amran Laga (jurnal1, 2019)
Rice straw is one of the lignocellulosic substrate that has not been used optimally and mostly just become an agricultural waste if not handled properly. Cellulose and hemicellulose content in lignocellulose structures of rice straw has great potential for thermostable enzymes production from thermophilic bacteria. The purpose of this study were to determine the effect of pretreatment in rice straw substrate on the total number of bacteria and its enzyme activity. The method used in this study include straw flour production, bacteria isolation and multi-level batch selection system, themostable enzyme production, total bacteria and enzyme activity measurement. The results obtained were combination of alkaline delignification and pressurized steam heating treatment resulting higher microbial growth pattern than the pressure steam heating only. Observation of pH showed pH decreasing in each treatment. The enzyme activity obtained showed fluctuating results due to the presence of diauxie phenomenon.